CTL10 has multiple functions in the innate immune responses of the silkworm, Bombyx mori. (February 2022) - Liu, Fang-Fang; Liu, Ze; Li, Hao; Zhang, Wen-Ting; Wang, Qian; Zhang, Bang-Xian; Sun, Yan-Xia; Rao, Xiang-Jun
Abstract: Insect C-type lectins (CTLs) play crucial roles in modulating the humoral and cellular immune responses. In the domesticated silkworm Bombyx mori L., BmCTL10 gene encodes an immulectin containing two carbohydrate recognition domains (CRDs). The phylogenetic analysis showed that BmCTL10 didn't cluster with other immulectin homologs in B. mori . BmCTL10 was mainly expressed in second to fifth instar larvae, wandering stage larvae, prepupa, and adults. In naïve fifth instar larvae, BmCTL10 was predominantly expressed in the fat body and epidermis. In second instar larvae, the topical application of Beauveria bassiana by immersion caused down-regulation of BmCTL10 . The intra-hemocoel injection of E. coli, S. aureus, B. bassiana, and 20-hydroxyecdysone in fifth instar larvae caused tissue and time-specific inductions. The recombinant protein (rBmCTL10) can bind to larval hemocytes and various pathogen-associated molecular patterns to enhance hemocyte-mediated nodulation, phagocytosis, and encapsulation. rBmCTL10 caused significant upregulation of most antimicrobial peptides and nitric oxide synthase 1 in hemocytes in vivo . Yeast two-hybrid demonstrated that integrin β3 and β4 subunits can interact with BmCTL10. Furthermore, only CRD2 can interact with the β3, while both CRD1 and CRD2 can interact with the β4. Taken together, this study showed that BmCTL10 has multiple functions in the innate immune responses of B. mori and two integrin β subunits are their potential receptors. Highlights: BmCTL10 binds to pathogen-associated molecular patterns and B. mori hemocytes. BmCTL10 induces bacterial agglutination in the presence of Ca 2+ . BmCTL10 can enhance nodulation, phagocytosis, and encapsulation. BmCTL10 can regulate immune genes expression in larval hemocytes. BmCTL10 interacts with integrin β3 and β4 subunits.